THE EFFECT OF CALCIUM AND PHOSPHORUS DIETARY LEVEL ON EGG PRODUCTION OF THE BANTUL LOCAL DUCK - Sasongko, H.; Yuwanta, T.; Zuprizal, Z.; Supadmo, S.; Widiyono, I. (Journal of the Indonesian Tropical Animal Agriculture, 2012)
This study was conducted to determine the effect of various calcium and phosphorus levels on theproduction performance of Bantul Duck. A total of 270 female ducks, 26 weeks age, were used in thestudy with a 3x3 factorial treatment, which is a combination of three levels of Ca: 3.75; 3.25 and 2.75%and three levels of P: 0.45, 0.35 and 0.25%. Each treatment occupied three replication cages, each ofwhich consisted of 10 ducks. The experiment was conducted for 12 weeks.. Data recorded were: (a) feedintake (g/duck/day), (b) egg production (% HDA), and (c) feed conversion. All quantitative dataobtained during the study were analyzed by analysis of variance (ANOVA) using SPSS computerprogram. The results of the variables recorded did not show significantly difference. Increasing Ca levelon feed showed an increasing trend of egg production. The average feed consumption ranged at 151-159g/duck/day; egg production was 75-84%, and the feed conversion was 184-212 g/egg.